Inhibition Zone Test of Ethyl Acetate Extract of White Frangipani (Plumeria acuminata) Against Candida albicans - Sila Paramita Dhayang Ganjar; Novitarini Novitarini; I Nyoman Bagus Aji Kresnapati (Universitas Islam Jember, 2026)
Candida albicans infection is a common health problem in Indonesia, particularly due to the tropical climate that supports fungal growth. The prevalence of candidiasis in Indonesia is approximately 20–25%. The use of synthetic antifungals such as ketoconazole is becoming increasingly limited because of the emergence of resistance and adverse side effects, creating the need for safer natural alternatives. One potential solution is the utilization of white frangipani (Plumeria acuminata), which is known to contain antifungal compounds such as flavonoids, alkaloids, and tannins. This study aimed to evaluate the effectiveness of ethyl acetate extract from white frangipani flowers against the growth of Candida albicans, as measured by the inhibition zones formed. The method used was a laboratory experimental design with well diffusion assays, applying various extract concentrations (25%, 50%, 75%, and 100%) against Candida albicans, followed by measuring the inhibition zone diameters. The results showed that increasing extract concentrations correlated with larger inhibition zone diameters, ranging from 16 mm at 25% concentration, 20.1 mm at 50%, 23.8 mm at 75%, and 27.5 mm at 100%. Based on these findings, it can be concluded that white frangipani flowers have potential as a natural antifungal alternative at all tested concentrations, with particularly strong effectiveness at 50%, 75%, and 100%. Therefore, white frangipani shows promise for further development as a herbal medicine.